Cutting through the noise: unravelling the web of misinformation in surgical social networks - Suárez-Gómez, Santiago A.; Velasco-Muñoz, Valentina; Restrepo-Vivas, Sara; Cabrera, Luis Felipe; Torregrosa, Lilian (Educación médica, 2025)
Social media, a pervasive platform for real-time communication, harbours both the potential for rapid information dissemination and the risk of spreading misinformation. While it has become an indispensable platform for global communication, concerns arise regarding its role in disseminating healthcare information. This study examines the impact of healthcare-related information on social media, particularly focusing on influential surgical accounts. It investigates the quality of content shared by these accounts and compares it with current scientific evidence. A retrospective study was conducted to evaluate the accuracy of information presented on platforms of influential surgical accounts on social media, including YouTube, TikTok, and Instagram. A sample of surgical influencers, encompassing general surgery and subspecialties, was examined. Their content was retrospectively compared against current scientific evidence related to their respective surgical topics. The evaluation reveals a diverse landscape regarding the accuracy of healthcare information shared by surgical influencers on social media. While some content aligns with evidence-based practices, there is a notable presence of misinformation and inaccuracies. This highlights the potential consequences of social media on healthcare information dissemination, emphasizing the importance of accurate and evidence-based content. The study acknowledges the significant influence of these accounts, especially among young people, and underscores the need for responsible information sharing in the medical field due to the potential impact of inaccurate content on healthcare decision-making. Surgical influencers often neglect to provide references of evidence-based information and instead rely on personal experience, posing risks of misinformation and ethical concerns on social media platforms. Las redes sociales, plataformas necesarias para la comunicación en tiempo real, albergan tanto el potencial para la rápida difusión de información como el riesgo de propagar desinformación. Aunque son indispensables para la comunicación global, surgen preocupaciones sobre su papel en la difusión de información del área de la salud. Este estudio examina el impacto de la información relacionada con la salud en las redes sociales, centrándose particularmente en cuentas de influencers con contenido quirúrgico, y analiza la calidad del contenido compartido por estas cuentas. Se llevó a cabo un estudio retrospectivo para evaluar la precisión de la información presentada en las plataformas de influencers con cuentas de contenido quirúrgico, incluyendo YouTube, TikTok e Instagram. Se examina una muestra de influencers quirúrgicos, abarcando cirugía general y subespecialidades. Su contenido se compara retrospectivamente con la evidencia científica actual relacionada con sus respectivos temas quirúrgicos. Se encontró un panorama diverso en las cuentas quirúrgicas en las redes sociales evaluadas. Si bien algunos contenidos se alinean con prácticas basadas en evidencia, existe una notable presencia de desinformación e inexactitudes. Esto destaca las posibles consecuencias de las redes sociales en la difusión de información sanitaria, enfatizando la importancia de un contenido preciso y basado en evidencia. Hay una influencia significativa de estas cuentas, especialmente entre los jóvenes, lo que implica la necesidad de compartir información responsable en el campo médico debido al potencial impacto de un contenido inexacto en la toma de decisiones sanitarias. Los influencers quirúrgicos a menudo descuidan proporcionar referencias de información basada en evidencia y prefieren utilizar experiencias personales, lo que plantea riesgos de desinformación y preocupaciones éticas en las plataformas de redes sociales.